2010
DOI: 10.1088/0960-1317/20/5/055006
|View full text |Cite
|
Sign up to set email alerts
|

An acceleration switch with a robust latching mechanism and cylindrical contacts

Abstract: A microelectromechanical systems acceleration latching switch with cylindrical contacts and an easy-latching/difficult-releasing (ELDR) latching mechanism is presented in this paper. The cylindrical contacts can make the switch immune to fabrication imperfections and off-axis shocks and can decrease the contact resistance as well. The ELDR latching mechanism can latch the switch reliably. Moreover, all the contacts and their support beams are separated from the proof mass so as to prevent the contacts from ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Xu et al [32] studied the energy dissipation of the latching process and concluded that the latches can greatly enhance the shock robustness of the switch compared with hard stops. Ma et al [33] used various polydimethylsiloxane (PDMS) caps to change the displacement state of the proof mass, thus enabling the adjustment of the acceleration threshold from 40 g to 75 g. Guo et al [34,35] designed the switch with multi-contacts independent to the proof-mass to prevent the contacts from the impact resulting from the rebound or vibration of the proof-mass once the switch was latched, and therefore the contact reliability was improved. The results showed that the contact resistance was less than 5 Ω while the isolation resistance was more than 200 MΩ, and the maximum allowable current was up to 100 mA.…”
Section: Persistent Closed Inertial Micro-switchesmentioning
confidence: 99%
“…Xu et al [32] studied the energy dissipation of the latching process and concluded that the latches can greatly enhance the shock robustness of the switch compared with hard stops. Ma et al [33] used various polydimethylsiloxane (PDMS) caps to change the displacement state of the proof mass, thus enabling the adjustment of the acceleration threshold from 40 g to 75 g. Guo et al [34,35] designed the switch with multi-contacts independent to the proof-mass to prevent the contacts from the impact resulting from the rebound or vibration of the proof-mass once the switch was latched, and therefore the contact reliability was improved. The results showed that the contact resistance was less than 5 Ω while the isolation resistance was more than 200 MΩ, and the maximum allowable current was up to 100 mA.…”
Section: Persistent Closed Inertial Micro-switchesmentioning
confidence: 99%
“…To achieve stable and low frequency trigger signals, two inertial switch structure design schemes are proposed. The first is a flexible contact scheme based on a non-silicon MEMS process from bottom to top [8,9,10], the other is a latching structure based on silicon etching [11,12]. The operating principles of above two designs are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The holding time is a critical parameter, and short holding time is an obstacle for circuit analyzing in many applications [14]. Mechanical latching switches and shock sensors have been proposed to prolong the holding time, as reported in the references [15]- [17], where the movable electrode and fixed electrode are latched when the inertial microswitch is closed. This design can prolong the holding time, but the microswitches are difficult to be reset.…”
Section: Introductionmentioning
confidence: 99%